KOHESIVITAS SUAMI ISTRI DI USIA MADYA - Anindita, Diah; Bashori, Khoiruddin (HUMANITAS (Jurnal Psikologi Indonesia), 2012)
In the middle age, adjustment to developmental tasks will affect maritalrelationship. This study aimed to determine the cohesiveness of husbandand wife who have entered middle adulthood, covering aspects of solidarity,marital satisfaction, interest, and affiliates and also the factors that affectthe cohesiveness of husband and wife when the marriage age of 20 yearsor more. Subjects are three pairs of husband and wife who are legallymarried for over 20 years and each individuals age between 40-60 yearsold. This qualitative research used the case study approach and collecteddata by semi-structured interviews and nonparticipant observation. Theresults showed that the cohesiveness of husband and wife owned in middleage is different in each pair. In the first couple showed low cohesion, highon the second couple, and medium for the third couple. In the third couple,there is a change before the peak of the conflict in mid-2011 by now.Factors that affect the cohesiveness of husband and wife in middle age is asocial perception, social support, emotional regulation, a period of quiet inthe middle ages, the intensity of togetherness, understanding of gender,temperament, and love.